Artificial Intelligence Enhanced Direct Current Fast ChargingIntegration for Electric Vehicles on 20 kV Grids: A Technical andOntological Study - Samsurizal Samsurizal; Arif Nur Afandi; Mohamad Rodhi Faiz (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
Ontological philosophy offers a conceptual foundation to reflect on the existence and evolution of electric vehicles (EVs) as intelligent energy entities. The transition to electric vehicles has attracted global attention, particularly regarding sustainability and energy efficiency. This paper presents a novel approach to integrating artificial intelligence (AI) with DC fast charging on a 20 kV grid, highlighting both ontological and engineering perspectives. It introduces a framework where electric vehicles are no longer passive tools but active energy entities optimized through AI for real-time energy distribution, improving efficiency and grid stability. The ontological investigation explores the essence of electric vehicles as entities that interact with electrical infrastructure while questioning their role in modern transportation systems and environmental paradigms. The study investigates the application of artificial intelligence in optimizing the performance and efficiency of direct current fast charging systems, addressing challenges associated with load balancing, network stability, and real-time data processing. Artificial intelligence algorithms enable intelligent decision-making for energy distribution, minimizing grid pressure while ensuring optimal charging speeds. By blending ontological philosophy with technology analysis, this paper offers insights into how artificial intelligence-driven systems are redefining the relationship between electric vehicles, high-voltage grids, and sustainable energy ecosystems. The findings highlight the potential of artificial intelligence to improve electric vehicle charging efficiency, grid integration, and long-term sustainability in the energy transition.